Acute Ethanol-Induced Changes in Edema and Metabolite Concentrations in Rat Brain. (25th March 2014) - Liu, Huimin; Zheng, Wenbin; Yan, Gen; Liu, Baoguo; Kong, Lingmei; Ding, Yan; Shen, Zhiwei; Tan, Hui; Zhang, Guishan
Abstract : The aim of this study is to describe the acute effects of EtOH on brain edema and cerebral metabolites, using diffusion weight imaging (DWI) and proton magnetic resonance spectroscopy ( 1 H-MRS) at a 7.0T MR and to define changes in apparent diffusion coefficient (ADC) values and the concentration of metabolites in the rat brain after acute EtOH intoxication. ADC values in each ROI decreased significantly at 1 h and 3 h after ethanol administration. ADC values in frontal lobe were decreased significantly compared with other regions at 3 h. For EtOH/Cr+PCr and cerebral metabolites (Cho, Tau, and Glu) differing over time, no significant differences for Ins, NAA, and Cr were observed in frontal lobes. Regression analysis revealed a significant association between TSEtOH/Cr+PCr and TSCho, TSTau, TSGlu, and TSADC . The changes of ADC values in different brain regions reflect the process of the cytotoxic edema in vivo. The characterization of frontal lobes metabolites changes and the correlations between TSEtOH/Cr+PCr and TSCho, TSTau, and TSGlu provide a better understanding for the biological mechanisms in neurotoxic effects of EtOH on the brain. In addition, the correlations between TSEtOH/Cr+PCr and TSADC will help us to understand development of the ethanol-induced brain cytotoxic edema.